Assessing the Effectiveness of Modified Tibial Plateau Leveling Osteotomy Plates for Treating Cranial Cruciate Ligament Rupture and Medial Patellar Luxation in Small-Breed Dogs - Eunbin Jeong; Youngjin Jeon; Taewan Kim; Dongbin Lee; Yoonho Roh (Animals, 2024)
In small-breed dogs with concurrent cranial cruciate ligament rupture (CCLR) and medial patellar luxation (MPL), correcting both disorders is are essential for restoring normal gait. However, the previously described surgical treatment, using two osteotomy technique, poses a high risk of fracture and instability. Addressing CCLR and MPL with a single osteotomy and implant was considered superior to the conventional method. Therefore, a pre-contoured modified tibial plateau leveling osteotomy (PCM–TPLO) plate facilitating medial shifting of the proximal tibia was developed. We compared postoperative alignment and strength between this novel plate group and a conventional tibial plateau leveling osteotomy (TPLO) plate group using eight small-breed dog cadavers each. Additionally, we investigated the potential of the novel plate as an alternative to tibial tuberosity transposition. Postoperative alignment and strength were assessed through radiographs and mechanical testing. Measurements including tibial plateau angle, mechanical medial proximal tibial angle, and number of screws within the joint were also analyzed. There were no significant differences in all measured parameters. For the novel plate, the medial displacement ratio of the proximal tibia was confirmed to be approximately 30%, and the result was thought to be appropriate. These findings suggest that the PCM–TPLO plate could be a promising alternative for treating concurrent CCLR and MPL in small-breed dogs.